Multiplicador dos gastos do governo em períodos de expansão e recessão: evidências empíricas para o Brasil - Grüdtner, Vanessa (2017)
In this dissertation I try to estimate a nonlinear transition autoregressive vector with a purpose of veriﬁcation if the Brazilian government expenditure multiplier is dependent of the economic cycle. The analysis period runs from the ﬁrst quarter of 1999 to the fourth quarter of 2015. In addition to the government’s consolidated costs, were calculated the multiplier for government’s consumption, government investment and wages paid by government to public employees. The results show that government spending multipliers behave in the same way in periods of recession and expansion. This result is robust to shocks in government spending given in periods of strong expansion and deep recession, the multiplier of government spending driven by investment, the debt/GDP ratio, and the degree of economic openness and exchange rate.